किचकवधका पुरातात्विक अवशेषहरु Archaeological Remains of the Kichakbadh - Baral, Deva Narayan (Nepalese Culture, 2023)
This academic article presents an explanatory research study on the archaeological artifacts discovered in the Kichakbadh area, situated in wards 2 and 3 of the Bhadrapur Municipality within the Jhapa district. The objective of this research is to examine the cultural and historical significance of Kichakbadh, shed light on its archaeological importance, and elucidate the various archaeological artifacts that have been unearthed to date. The excavations carried out by the Department of Archaeology have revealed the ruins of buildings, a walled complex, and remnants of bricks and pottery. Although it is traditionally believed that there is Natiyashala (Theatre) or palace of king Birat of Mahabharat. The derived archaeological evidences indicate that it could be archaeological site belonging to Sunga/Kushan Period. This academic research study utilizes qualitative methods and draws on both primary and secondary sources form of  data.It adopts a post-positivist research paradigm and employs analytical and descriptive methods to present its findings. This scholarly inquiry contributes new knowledge to the current context and enhances our understanding of the archaeological significance of Kichakbadh.